The three-dimensional structure of subjective wellbeing - Rodríguez Fernández, Arantzazu; Goñi Grandmontagne, Alfredo (Anales de Psicología / Annals of Psychology, 2011)
The issue of subjective wellbeing has recently been attracting a considerable amount of interest in psychological studies, and important progress has been made in our knowledge of this phenomenon. Empirical corroboration is required, however, in order to support some of the dif-ferent models which have been proposed in relation to its internal organi-zation. This study aims to verify a three-dimensional theoretical model of subjective wellbeing, consisting of life satisfaction, positive affect and negative affect. A total of 1178 students aged between 12 and 23 partici-pated in the study. Of these, 780 were female and 398 male. The results of the confirmatory factorial analyses indicate that this theoretical model, based on three independent dimensions, offers a better fit for the data than other alternative models.